Effect of various dietary fats on fatty acid profile in duck liver: Efficient conversion of short-chain to long-chain omega-3 fatty acids - Chen, Xi; Du, Xue; Shen, Jianliang; Lu, Lizhi; Wang, Weiqun (My University, 2016)
Omega-3 fatty acids, especially long-chain omega-3 fatty acids, have been associated with potential health benefits for chronic disease prevention. Our previous studies found that dietary omega-3 fatty acids could accumulate in the meat and eggs in a duck model. This study was to reveal the effects of various dietary fats on fatty acid profile and conversion of omega-3 fatty acids in duck liver. Female Shan Partridge Ducks were randomly assigned to five dietary treatments, each consisting of 6 replicates of 30 birds. The experimental diets substituted the basal diet by 2% of flaxseed oil, rapeseed oil, beef tallow, or fish oil, respectively. In addition, a dose response study was further conducted for flaxseed and fish oil diets at 0.5%, 1%, and 2%, respectively. At the end of the five-week treatment, fatty acids were extracted from the liver samples and analyzed by GC-FID. As expected, the total omega-3 fatty acids and the ratio of total omega-3/omega-6 significantly increased in both flaxseed and fish oil groups when compared with the control diet. No significant change of total saturated fatty acids or omega-3 fatty acids was found in both rapeseed and beef tallow groups. The dose response study further indicated that 59Ð81% of the short-chain omega-3 ALA in flaxseed oil-fed group was efficiently converted to long-chain DHA in the duck liver, whereas 1% of dietary flaxseed oil could produce an equivalent level of DHA as 0.5% of dietary fish oil. The more omega-3 fatty acids, the less omega-6 fatty acids in the duck liver. Taken together, this study showed the fatty acid profiling in the duck liver after various dietary fat consumption, provided insight into a dose response change of omega-3 fatty acids, indicated an efficient conversion of short- to long-chain omega-3 fatty acid, and suggested alternative long-chain omega-3 fatty acid-enriched duck products for human health benefits.
Citation: Chen, X., Du, X., Shen, J., Lu, L., & Wang, W. (2016). Effect of various dietary fats on fatty acid profile in duck liver: Efficient conversion of short-chain to long-chain omega-3 fatty acids. Experimental Biology and Medicine, 1535370216664031. https://doi.org/10.1177/1535370216664031
Keywords: Omega-3 Fatty Acid; Duck; Liver; Dietary Fat; Health Benefits